2016
DOI: 10.1016/j.jbiomech.2015.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of LifeAct-GFP and actin-GFP on cell mechanics assessed using micropipette aspiration

Abstract: The actin cytoskeleton forms a dynamic structure involved in many fundamental cellular processes including the control of cell morphology, migration and biomechanics. Recently LifeAct-GFP (green fluorescent protein) has been proposed for visualising actin structure and dynamics in live cells as an alternative to actin-GFP which has been shown to affect cell mechanics. Here we compare the two approaches in terms of their effect on cellular mechanical behaviour. Human mesenchymal stem cells (hMSCs) were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 35 publications
(48 reference statements)
2
47
0
Order By: Relevance
“…Using the example of LifeAct, it has been proposed to be the most suitable actin probe to visualize the dynamic rearrangement of the actin cytoskeleton in Dictyostelium, as it labels a more complete subset of actin structures than other actin-binding probes (Lemieux et al, 2014). The application of LifeAct was also favored over actin fused to fluorophore in the context of visualizing actin rearrangements during cellular mechanotransduction events (Sliogeryte et al, 2016;Deibler et al, 2011). In contrast, LifeAct should be used with caution for actin visualization in fission yeast, as it can cause severe concentration-dependent defects in endocytosis and cytokinesis (Courtemanche et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the example of LifeAct, it has been proposed to be the most suitable actin probe to visualize the dynamic rearrangement of the actin cytoskeleton in Dictyostelium, as it labels a more complete subset of actin structures than other actin-binding probes (Lemieux et al, 2014). The application of LifeAct was also favored over actin fused to fluorophore in the context of visualizing actin rearrangements during cellular mechanotransduction events (Sliogeryte et al, 2016;Deibler et al, 2011). In contrast, LifeAct should be used with caution for actin visualization in fission yeast, as it can cause severe concentration-dependent defects in endocytosis and cytokinesis (Courtemanche et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, GFP-actin is suitable for fluorescence recovery after photobleaching (FRAP) approaches to study actin dynamics and turnover within a given cellular F-actin structure, including, for instance, the actin cortex (Clark et al, 2013) or protrusions such as lamellipodia (Koestler et al, 2009) (see poster). However, the relatively large size (∼28 kDa) of GFP-like proteins (Sliogeryte et al, 2016) can give rise to problems in terms of incorporation of GFP-tagged actin monomers into filaments. Thus, the GFP-actin-derived localization pattern might only reflect a part of the total F-actin network in cells.…”
Section: Live-cell Imaging Using Gfp-actin Derivativesmentioning
confidence: 99%
“…To assess lamellipodial dynamics, smooth muscle cells were co-transfected with plasmids encoding EGFP-tagged recombinant GMF γ and LifeAct-RFP plasmid, which generates a 17 amino-acid peptide to visualize F-actin in live cells 52 . Live-cell confocal and TIRF microscopy of cells expressing WT-GMF γ revealed that the majority localized to both the near membrane region of the ventral side of the cell, and within lamellipodia and filopodia (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While studies have revealed differing stiffnesses in immobilized cells 5255 and differing deformabilities in suspended cells, 5658 for instance comparing healthy and cancerous cells or different cancer cells, the particular length and time scales of the deformation is often not clear and is critical. Specific separations strategies distinguish only a particular range in cell properties: The deformations relevant to our method could be as small as a few nanometers, evidenced by the sensitivity to ionic strength.…”
Section: Discussionmentioning
confidence: 99%